Discoveries of Extrachromosomal Circles of DNA in Normal and Tumor Cells. Issue 4 (April 2018) - Paulsen, Teressa; Kumar, Pankaj; Koseoglu, M. Murat; Dutta, Anindya
Abstract : While the vast majority of cellular DNA in eukaryotes is contained in long linear strands in chromosomes, we have long recognized some exceptions like mitochondrial DNA, plasmids in yeasts, and double minutes (DMs) in cancer cells where the DNA is present in extrachromosomal circles. In addition, specialized extrachromosomal circles of DNA (eccDNA) have been noted to arise from repetitive genomic sequences like telomeric DNA or rDNA. Recently eccDNA arising from unique (nonrepetitive) DNA have been discovered in normal and malignant cells, raising interesting questions about their biogenesis, function and clinical utility. Here, we review recent results and future directions of inquiry on these new forms of eccDNA. Highlights: Genome sequencing, microscopic and biochemical methods have identified eccDNA in a wide range of species, tissues, and cells. eccDNA is present in tumor cells and larger eccDNA harbors oncogenes. eccDNA is heterogeneous in size, ranging from a few hundred (microDNA) to a few megabases (DMs). Some eccDNA has a role in conferring tumor drug resistance. eccDNA may provide genetic diversity between cells even in normal tissues.